2005
DOI: 10.1213/01.ane.0000160535.95678.34
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Versus Epidural Anesthesia for Cesarean Delivery in Severe Preeclampsia: A Prospective Randomized, Multicenter Study

Abstract: In this randomized, multicenter study we compared the hemodynamic effects of spinal and epidural anesthesia for cesarean delivery in severely preeclamptic patients. The epidural group (n = 47) received 2% lidocaine with epinephrine 1:400,000, 18-23 mL, followed by 3 mg of morphine after delivery. The spinal group (n = 53) received 2.2 mL of 0.5% hyperbaric bupivacaine plus 0.2 mg morphine. We hypothesized that the lowest MAP (mean arterial blood pressure, the primary outcome) during the delivery period would h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 12 publications
1
38
0
1
Order By: Relevance
“…Fourthly, the increased willingness to do emergent spinal anesthesia including intentional continuous spinal techniques, especially in individuals with certain comorbid conditions (e.g. severe preeclampsia and morbid obesity), [16][17][18] may have been partly responsible for this reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, the increased willingness to do emergent spinal anesthesia including intentional continuous spinal techniques, especially in individuals with certain comorbid conditions (e.g. severe preeclampsia and morbid obesity), [16][17][18] may have been partly responsible for this reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive monitoring detects rapid haemodynamic changes and allows early treatment during the evolving block. 4,5 Aggressive intravenous fluid loading may increase the risk of pulmonary oedema in these patients secondary to low plasma oncotic pressure and increased permeability of pulmonary alveolar capillaries. 6 Roofthooft and Van de Velde reported that when bupivacaine 6.5 mg was given with sufentanil as part of a combined spinal-epidural (CSE) technique, the need to top-up the epidural catheter was rare if surgery finished within 60 min.…”
mentioning
confidence: 99%
“…Traditional concerns over avoiding spinal anesthesia due to excessive hypotension do not appear to have been warranted. Although Visalyaputra et al [69] found that significant hypotension (systolic \100 mmHg) was more frequent among patients receiving spinal rather than epidural anesthesia (51 vs. 23 %; P = 0.004), these episodes of hypotension lasted less than one minute and were easily treated (with 6 vs. 12 mg ephedrine). In addition, newborn outcomes were similar in both groups.…”
Section: Cesarean Anesthesiamentioning
confidence: 94%
“…Regional techniques for delivery via cesarean section are preferred over general anesthesia, as there appears to be fewer morbid complications [68]. In the patient with severe preeclampsia, spinal anesthesia results in similar hemodynamic stability as either epidural or general anesthesia [69][70][71]. Traditional concerns over avoiding spinal anesthesia due to excessive hypotension do not appear to have been warranted.…”
Section: Cesarean Anesthesiamentioning
confidence: 99%